KEMAMPUAN MENYELESAIKAN SOAL CERITA MATEMATIKA LITERASI FINANSIAL - Izzatunnisa; Feny Rita Fiantika; Prayogo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the ability to solve math story problems on financial literacy skills in grade IV students at SDN Sedati Gede II. Financial literacy is an important skill needed to understand, manage and make wise financial decisions. The ability to solve math story problems is considered relevant in improving financial literacy because it involves logical thinking, analytical processes, and the application of mathematical concepts in the context of everyday life. This study used a quantitative method with a correlational design. Data were collected through a test of the ability to solve math story problems and a financial literacy test. The research sample was fourth grade students who were selected using cluster sampling technique. Data analysis was carried out using simple linear regression techniques to determine the relationship and influence between the two variables. The results showed that the results of the simple linear regression equation the value of component a (constant) was 39.878 and the value of component b (regression coefficient) was 0.616. In calculating the regression value, the regression equation is obtained: Y = 39.878 + 0.616X (Y = a + bX) there is a significant positive influence between the ability to solve math story problems on financial literacy skills. This indicates that the higher the students' ability to solve math story problems, the better their financial literacy. This study suggests that educators can integrate the concept of financial literacy into mathematics learning, especially through story problems that are relevant to everyday life.